2018
DOI: 10.1183/13993003.01788-2018
|View full text |Cite
|
Sign up to set email alerts
|

Cloud algorithm-driven oximetry-based diagnosis of obstructive sleep apnoea in symptomatic habitually snoring children

Abstract: The ability of a cloud-driven Bluetooth oximetry-based algorithm to diagnose obstructive sleep apnoea syndrome (OSAS) was examined in habitually snoring children concurrently undergoing overnight polysomnography.Children clinically referred for overnight in-laboratory polysomnographic evaluation for suspected OSAS were simultaneously hooked to a Bluetooth oximeter linked to a smartphone. Polysomnography findings were scored and the apnoea/hypopnoea index (AHIPSG) was tabulated, while oximetry data yielded an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Machine learning approaches are increasingly used for diagnosis, disease risk classification, and therapeutic guidance 21,46 and are especially promising in sleep medicine. 22,23,47,48 Downloaded From: https://jamanetwork.com/ on 09/16/2020 with other OSA diagnostic systems, as well as reducing medical errors by facilitating the complex process of respiratory event scoring.…”
Section: Comparison Of Sunrise System With Other Osa Diagnostic Systemsmentioning
confidence: 99%
“…Machine learning approaches are increasingly used for diagnosis, disease risk classification, and therapeutic guidance 21,46 and are especially promising in sleep medicine. 22,23,47,48 Downloaded From: https://jamanetwork.com/ on 09/16/2020 with other OSA diagnostic systems, as well as reducing medical errors by facilitating the complex process of respiratory event scoring.…”
Section: Comparison Of Sunrise System With Other Osa Diagnostic Systemsmentioning
confidence: 99%
“…In the present study, we focus on the usefulness of blood oxygen saturation (SpO 2 ) and airflow, which are commonly involved in type IV devices. Individually, both signals have been found to provide relevant information for OSA diagnosis [9][10][11][12] . Notwithstanding, the potential complementarity of the features derived from both signals has been marginally studied 13 .…”
mentioning
confidence: 99%
“…On the other hand, the MLP neural networks used in previous approaches tended to overestimate the severity of OSA [ 29 , 32 , 42 ]. Vaquerizo-Villar et al reported 12.75% of underestimated subjects and 27.30% of overestimated patients [ 29 ], while in Xu et al the rates of underestimated and overestimated severity were 15.05% and 31.25%, respectively [ 42 ]. In our study, this behavior was not observed, since AdaBoost achieved a more balanced ratio of underestimated and overestimated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches included Logistic Regression (LR) [ 23 , 24 , 25 , 27 , 28 , 30 , 31 , 36 , 37 ], Linear or Quadratic Discriminant Analysis (LDA, QDA) [ 38 , 39 , 40 ], and Support Vector Machines (SVM) [ 41 ]. Other recent studies relied on more complex Multilayer Perceptron (MLP) neural networks [ 26 , 29 , 32 , 42 , 43 ]. Most of these algorithms can be hardly generalizable due to their simplicity and susceptibility to overfitting the training data [ 44 ].…”
Section: Introductionmentioning
confidence: 99%